Composites from polypropylene (PP) reinforced with oil palm empty fruit bunch (OPENFB) fibre - Nora'asheera, Mohd Nazif (2011)
The use of natural fibers obtained from plants and trees are reinforcing materials has attracted many researcher to widen their applications. Natural fibers are low cost, low density, have high specific properties, biodegradable and non-abrasive. Oil palm fiber (OPF) can be obtained directly from natural resource; it is cheap and also has advantages due to its renewable nature, low cost and easy viability. The study aims to give the improvement to composite from plastic reinforced with oil palm empty fruit bunch along with to determine the mechanical performances of the composite. In this research, the sample will through the alkali treatment using sodium hydroxide (NaOH) follow by hydrogen peroxide (H2O2) and the last is using acetic acid (C2H4O2). NaOH is use as a solvent extraction and it will break the lignin bonding. Remove lignin will decrease the absorption of water in composite. Addition different type plasticizer and MAPP will give better improvement to mechanical performance to composite. From the analysis that have done, compatibilized and plasticizers systems an enhanced fibre dispersion and interfacial adhesion has been observed, supporting the occurrence of effective interactions between the functional groups on the copolymer chains and the polar groups of the fibres, as demonstrated by FT-IR analysis. Besides that, the density and melt flow index of composites with different plasticizer was determined and from the all test that have been done it showed that polyethylene glycol is the good plasticizers compared to sorbitol and glycerol.